Peran Tokoh Agama dalam Pembinaan Etika Remaja di Desa Sinah Kasih Kecamatan Sei Rampah - Ritonga, Mitta Syahrani; Adenan, Adenan; Harahap, Salahuddin (ANWARUL, 2023)
Sinah Kasih Village is included in the Sei Rampah subdistrict, most of the residents of this village have a livelihood by gardening. Currently Sinah Kasih village is led by Mrs. Rahmawati, S.Pd.I as the village head. Sinah Kasih is part of a plantation company called PT. Soeloeng Laoet. This study uses a qualitative method, which aims to determine the influence of religious leaders in developing youth ethics in Sinah Kasih Village, Sei Rampah District. The purpose of this research was carried out because there were many fights and delinquency against teenagers in Sinah Kasih Village. For this reason, this study aims to find out the role of religious leaders in fostering adolescent ethics in the village of Sinah Kasih. The results of this study are that the role of religious leaders in fostering youth ethics in Sinah Kasih village is very influential, for this reason religious leaders provide religious guidance to adolescents and invite youth to pray in congregation at the mosque. From that, little by little the youth in Sinah Kasih village were able to control their emotions.